Women in Student Leadership: Challenges and Opportunities for Changing Campus Dynamics in the Modern Era - Habibah, Ihda Filzafatin (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 4 No 1 (2024): Proceeding of International Conference on Engineering, Technology, and Social Science 2024, 2025)
The role of women in various aspects of life continues to increase in today's modern era, but it is different with their participation in student leadership in the campus environment which still faces various challenges even though there are also opportunities. Patriarchal cultures, gender stereotypes, and a lack of structural support are often barriers for women to take leadership positions, especially within the campus sphere. This research aims to examine the role of women in student leadership in the campus environment, focusing on the challenges faced and opportunities that arise in the modern era. As the smallest scope with strategic prospects in shaping the next generation of leaders, student leadership reflects the social dynamics that are developing in society. However, women often face a variety of structural, cultural, and personal barriers that limit their participation in leadership positions. This study uses a qualitative approach with in-depth interviews with female students who are active in campus organizations, as well as analysis of organizational policies and culture. The results show that while challenges such as gender stereotypes, underrepresentation, and double burdens are still significant, there is a great opportunity for women to bring new perspectives, promote inclusivity, and drive positive change in campus leadership dynamics. As such, women can play an increasingly important role in shaping the future of a progressive and gender-equitable campus and an equal scope.